c y Gary Lewis. - Lewis, Gary (Emeryville, California : Rockridge Press, 2019)
A field guide to rocks and minerals for young readers.
Includes indexes.
Keywords: Rocks -- Juvenile literature; Minerals -- Juvenile literature